2020
DOI: 10.1016/s1473-3099(20)30019-0
|View full text |Cite
|
Sign up to set email alerts
|

Safety, reactogenicity, and immunogenicity of a chimpanzee adenovirus vectored Ebola vaccine in children in Africa: a randomised, observer-blind, placebo-controlled, phase 2 trial

Abstract: Background During the large 2013-16 Ebola virus outbreak caused by the Zaire Ebola virus, about 20% of cases were reported in children. This study is the first, to our knowledge, to evaluate an Ebola vaccine in children younger than 6 years. We aimed to evaluate the safety, reactogenicity, and immunogenicity of a monovalent, recombinant, chimpanzee adenovirus type-3 vectored Zaire Ebola glycoprotein vaccine (ChAd3-EBO-Z) in a paediatric population.Methods This phase 2, randomised, observer-blind, controlled tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 14 publications
3
41
0
1
Order By: Relevance
“…Most of the reported local and systemic adverse events were mild to moderate in severity, in line with our previous phase 1 study of the ChAdOx1 nCoV-19 vaccine 18 and previously reported studies of ChAdOx1-vectored vaccines. [22][23][24] Fewer adverse events were reported after the boost vaccination than after the prime vaccination and reactogenicity reduced with increasing age. The lower dose of vaccine was less reactogenic than the standard dose of vaccine across all age groups.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the reported local and systemic adverse events were mild to moderate in severity, in line with our previous phase 1 study of the ChAdOx1 nCoV-19 vaccine 18 and previously reported studies of ChAdOx1-vectored vaccines. [22][23][24] Fewer adverse events were reported after the boost vaccination than after the prime vaccination and reactogenicity reduced with increasing age. The lower dose of vaccine was less reactogenic than the standard dose of vaccine across all age groups.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to their lower seroprevalence and thus decreased vector neutralization in humans as compared to human Ad5, chimpanzee Ad (ChAd) vectors represent an attractive vaccine platform (3)(4)(5). ChAdvectored candidate vaccines against infectious diseases such as malaria, Ebola, and RSV have shown favorable immunogenicity and tolerability in humans (6)(7)(8)(9)(10)(11). These vaccines drive robust intracellular antigen expression, thus promoting a CD8 + T-cellbiased response, but were also shown to induce antigen-specific CD4 + T-cell responses and antibodies.…”
Section: Introductionmentioning
confidence: 99%
“…This antigen is then either secreted, induc- In children, vector-based vaccines have been tested against malaria, 49,50 tuberculosis, 51 and Ebola. 52,53 The malaria vaccine candidate ME-TRAP, based on a heterologous prime-boost schema with MVA and FP9, was shown to be safe and relatively immunogenic, 54,55 but not efficacious. 50 Against tuberculosis, the MVA-Ag85A vaccine was safe in children (n = 24, 1-7 y/o) and adolescents (N = 12, 13-15 y/o), initiating CD4 + T-cell responses that were moderately sustained at 6 months in adolescents.…”
Section: Vir Al Vec Tor-ba S Ed Vaccine Smentioning
confidence: 99%
“…In children, vector‐based vaccines have been tested against malaria, 49,50 tuberculosis, 51 and Ebola 52,53 . The malaria vaccine candidate ME‐TRAP, based on a heterologous prime‐boost schema with MVA and FP9, was shown to be safe and relatively immunogenic, 54,55 but not efficacious 50 .…”
Section: Viral Vector‐based Vaccinesmentioning
confidence: 99%
See 1 more Smart Citation